Muscle strength, level of pain and balance in women with knee osteoarthritis after a sensory-motor exercise program associated to photobiomodulation therapy via cluster: a single-blinded randomized with placebo control trial - Ana Beatriz Balão; Patricia Gabrielli Vassão; Marcela Regina de Camargo; Victor Zuniga Dourado; Helga Tatiane Tucci; Ana Cláudia Muniz Rennó (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2023)
Introduction: Osteoarthritis (OA) is the most common chronic condition of the joints that leads to pain, stiffness and disability.  Aim: The aim of this study was to determine the effectiveness of a sensory-motor exercises program and the photobiomodulation on pain, muscle strength, severity of the injury and dynamic balance of women with knee osteoarthritis.  Method and Materials: Thirty-two women were randomized in sensory-motor exercises associated with the placebo photobiomodulation group (SMAG) and sensory-motor exercises with the active photobiomodulation group (SMPG). The pain, knee flexor and extensor peak torque, severity of the injury and dynamic balance were evaluated with the numeric pain rating scale, cell roll, Knee Injury and Osteoarthritis Outcome Score and timed up and go, respectively. Subjects were administered sensory-motor exercises, strengthening exercises and photobiomodulation via cluster applied at the end of each training session for 8 weeks, 2 times/week.  Results: There was no significant improvement in the knee flexor and extensor peak torque, meantime, there was a significant linear positive correlation in the sensory-motor exercises program associated with the placebo photobiomodulation group (p = 0.002) at the end of treatment. A significant improvement in the severity of injury (p = 0.002) and dynamic balance (p = < 0.001) was observed in both groups. Furthermore, the level of pain showed a significant improvement in the sensory-motor exercises program associated with the placebo photobiomodulation group (p = 0.043).  Conclusion: Sensory-motor exercise program promotes beneficial effects on the severity of the injury and dynamic balance and its association with photobiomodulation was able to produce an extra effect in pain relief. However, adding photobiomodulation to routine exercise regimes for subjects with knee osteoarthritis should be investigated.